2006
DOI: 10.1039/b516328e
|View full text |Cite
|
Sign up to set email alerts
|

Migratory insertion in N-heterocyclic carbene-containing Fe carbonyl complexes: an experimental and theoretical study

Abstract: The compound [Fe(eta-C5H5)(CO)2(Me)] reacts thermally with N-heterocyclic carbenes (L) to give both alkyl, [Fe(eta-C5H5)(L)(CO)(Me)], and acyl, [Fe(eta-C5H5)(L)(CO)(COMe)], derivatives. The reaction temperature has been shown to affect the product distribution. The alkyl and acyl derivatives exist in an equilibrium that is more easily perturbed than in the tertiary phosphine analogues. DFT studies on the reactivity of [Fe(eta-C5H5)(CO)2(Me)] with PH3 and dihydroimidazole-2-ylidene (IH) have shown that CO excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 32 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…A small number of examples of bis‐carbene iron complexes12 has been synthesized. The first examples of mono‐carbene complexes were reported in 2003 by Guerchais13 which was followed by examples from Albrecht14, Llewellyn,15 and more recently the groups of Cesar and Lavigne16 and Ohki andTatsumi 17. Up to now, they were used in only very few examples as catalysts 17,18…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…A small number of examples of bis‐carbene iron complexes12 has been synthesized. The first examples of mono‐carbene complexes were reported in 2003 by Guerchais13 which was followed by examples from Albrecht14, Llewellyn,15 and more recently the groups of Cesar and Lavigne16 and Ohki andTatsumi 17. Up to now, they were used in only very few examples as catalysts 17,18…”
Section: Methodsmentioning
confidence: 98%
“…A small number of examples of bis-carbene iron complexes [12] has been synthesized. The first examples of mono-carbene complexes were reported in 2003 by Guerchais [13] which was followed by examples from Albrecht [14] , Llewellyn, [15] and more recently the groups of Cesar and Lavigne [16] and Ohki andTatsumi.[17] Up to now, they were used in only very few examples as catalysts. [17,18] Our interest in iron catalysis [19] and especially hydrosilylation [20,21] prompted us to examine the possibility of using NHC well-defined iron complexes in the hydrosilylation reaction.…”
mentioning
confidence: 99%
“…12 upon photoinduced cleavage of one Fe-CO bond and coordination of iodide. Following this report, our group [62][63][64][65][66] and others have expanded the scope of this synthesis by varying the wingtip substituents, [67,68] heterocyclic framework, [66,[69][70][71] co-ligands [71] and installing chelating groups to form dicarbene, [72] picolyl-carbene, [62] and pyridine-carbene complexes. [64] We have further demonstrated that bimetallic complexes can be accessed using dicarbene ligands with either flexible (13) electron complex is smoothly converted to the air-stable 18e − species 19 when exposed to a CO atmosphere.…”
Section: Scheme 6 Synthesis Of Imidazolylidene and Imidazolinylidenementioning
confidence: 99%
“…For a related structure with a 1,3-(2,6-diisopropylphenyl)imidazolidinium unit, see: Giffin et al (2010). For its synthesis, see: Llewellyn et al (2006). Data collection: APEX2 (Bruker, 2005); cell refinement: SAINT (Bruker, 2005); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: SHELXTL (Sheldrick, 2008); software used to prepare material for publication: SHELXTL.…”
Section: Related Literaturementioning
confidence: 99%